Pravna država in pravno načelo zaupanja v pravo - Spruk, Jure (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
The article discusses the connection between the legal state (and the rule of law) and the legal principle of trust in law in constitutional democracy. The legal state and the rule of law express central quality of the modern state in which a man is finally freed from religious predestination and natural determinism. Man’s freedom goes hand by hand with his responsibility for managing of the state, which is accomplished mainly through the application of law. Trust in law is one of the corner stones of society’s binder in the absence of which the law loses its function of coordinating in the state and in society. Trust in law means to trust another human being, whereas the legal principle of trust in law defends this sociological minimum through strengthening predictability and stability of legal norms.
Keywords: demokracija; pravna država; ustava; vladavina prava